Konsep Keseimbangan (Mīzān) dalam Islam sebagai Dasar Pembangunan Berkelanjutan - Wulan, Sri Ratna (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Within Islamic perspective, the principle of mīzān (balance) serves as a crucial conceptual foundation for achieving sustainable development through a holistic approach that integrates ecological, social, and economic dimensions. This study aims to comprehensively explore the essence of mīzān while examining its implementation within sustainable development frameworks. Employing qualitative methodology, the research conducts document analysis of Qur’anic verses, exegetical literature (tafsīr), and relevant scholarly works on sustainable development. The findings reveal that mīzān encompasses principles of social justice, moderation, and humanity’s role as stewards (khalīfah) of the Earth in preserving ecological balance. The application of this concept provides both ethical guidance and practical solutions for addressing contemporary environmental and social challenges. However, persistent obstacles—including inadequate environmental awareness and weak inter-institutional collaboration—require deeper internalization of Islamic values. The implementation of mīzān offers a viable ethical framework and actionable approach to confronting current socio-environmental issues.This study contributes to the discourse on Islamic-based sustainable development by bridging theoretical principles with practical applications.